Reply to discussion "Is spreading prolong, episodic or incipient in the Andaman Sea? Evidence from deepwater sedimentation" by J.R. Curray 2015 - C. K. Morley (2018)
© 2015 Elsevier Ltd. We consider the presence of thick section in the axial trough indicates that the Pliocene-Recent continuous spreading model proposed by Curray (2015) is not appropriate for the Andaman Sea. The high frequency of eustatic sea level changes during the Plio-Pleistocene is incompatible with large, rapid influxes of sediment, widely separated in time but related to eustacy as proposed by Curray (2015). Instead spreading is probably of Miocene age, and was only renewed recently, if at all. The nature of the crust adjacent to the spreading centre remains uncertain. However, industry seismic data from the East Andaman Basin strongly suggests if the western part of the basin is underlain by oceanic crust it must be Oligocene or older, it is not Early Miocene. This in turn suggests the volcanics dredged from the Alcock rise were extruded onto older crust (whether it is oceanic, island arc or continental), and do not represent the age of oceanic crust formation. Gravity and seismic reflection data point to the East Andaman Basin being dominantly underlain by extended, to hyper extended continental crust and transitional crust. The Alcock and Sewell rises are interpreted as representing the western side of the strongly necked zone of continental crust.